Impact of nasal symptoms on the evaluation of asthma control. Issue 8 (February 2017) - Huang, Chien-Chia; Chang, Po-Hung; Wu, Pei-Wen; Wang, Chun-Hua; Fu, Chia-Hsiang; Huang, Chi-Che; Tseng, Hsiao-Jung; Lee, Ta-Jen
Abstract : Abstract: The united airways concept suggests that patients with asthma typically exhibit parallel inflammation in the upper airway. The resulting nasal symptoms should reduce quality of life and substantially affect the evaluation of asthma control among these patients. This study aimed to assess the association of nasal symptoms with the evaluation of asthma control. Fifty-eight patients with asthma and persistent nasal symptoms were prospectively recruited for evaluations of their sinonasal symptoms and asthma control in a cross-sectional study from August 2013 to June 2016. Participants underwent thorough nasal endoscopy, sinus computed tomography, pulmonary function testing, the asthma control test (ACT), and the Sino-Nasal Outcome Test-22 (SNOT-22) questionnaires to evaluate their asthma control and sinonasal symptoms. There was a significant association between ACT and SNOT-22 scores. Among patients with asthma and chronic rhinosinusitis, ACT scores were closely related to the symptoms of cough, post-nasal discharge, dizziness, waking up at night, absence of a good night's sleep, and waking up tired. Among patients with asthma and chronic rhinitis, the forced expiratory volume in 1 second was closely related to the symptoms of needing to blow nose, runny nose, and cough. Patients with emergency clinic visits during the previous 3 months had relatively high SNOT-22 scores, especially for the symptoms of sneezing, runny nose, nasal blockage, cough, and dizziness. Sinonasal symptom severity was closely associated with measured asthma control status among patients with asthma and persistent nasal symptoms. Therefore, upper and lower airway inflammations should be considered and treated simultaneously.